Treatment of Sarcopenia with Bimagrumab: Results from a Phase II, Randomized, Controlled, Proof‐of‐Concept Study. Issue 9 (27th June 2017) - Rooks, Daniel; Praestgaard, Jens; Hariry, Sam; Laurent, Didier; Petricoul, Olivier; Perry, Robert G.; Lach‐Trifilieff, Estelle; Roubenoff, Ronenn
Abstract : Objectives: To assess the effects of bimagrumab on skeletal muscle mass and function in older adults with sarcopenia and mobility limitations. Design: A 24‐week, randomized, double‐blind, placebo‐controlled, parallel‐arm, proof‐of‐concept study. Setting: Five centers in the United States. Participants: Community‐dwelling adults (N = 40) aged 65 and older with gait speed between 0.4 and 1.0 m/s over 4 m and an appendicular skeletal muscle index of 7.25 kg/m 2 or less for men and 5.67 kg/m 2 or less for women. Intervention: Intravenous bimagrumab 30 mg/kg (n = 19) or placebo (n = 21). Measurements: Change from baseline in thigh muscle volume (TMV), subcutaneous and intermuscular fat, appendicular and total lean body mass, grip strength, gait speed, and 6‐minute walk distance (6MWD). Results: Thirty‐two (80%) participants completed the study. TMV increased by Week 2, was sustained throughout the treatment period, and remained above baseline at the end of study in bimagrumab‐treated participants, whereas there was no change with placebo treatment (Week 2: 5.15 ± 2.19% vs −0.34 ± 2.59%, P < .001; Week 4: 6.12 ± 2.56% vs 0.16 ± 3.42%, P < .001; Week 8: 8.01 ± 3.70% vs 0.35 ± 3.32%, P < .001; Week 16: 7.72 ± 5.31% vs 0.42 ± 5.14%, P < .001; Week 24: 4.80 ± 5.81% vs −1.01 ± 4.43%, P = .002). Participants with slower walking speed at baseline receiving bimagrumab had clinically meaningful and statistically significantly greater improvements in gait speed (mean 0.15 m/s, P = .009) and 6MWD (mean 82 m, P = .022) than those receiving placebo at Week 16. Adverse events in the bimagrumab group included muscle‐related symptoms, acne, and diarrhea, most of which were mild in severity and resolved by the end of study. Conclusion: Treatment with bimagrumab over 16 weeks increased muscle mass and strength in older adults with sarcopenia and improved mobility in those with slow walking speed.